METAL POLLUTION ASSESSMENT IN SEDIMENTS OF KARACHI COAST, PAKISTAN - Mashiatullah, A.; Chaudhary, M. Z.; Javed, T.; Ghaffar, A.; Khan, M. S.; Ahmad, N.; Qureshi, R. M. (The Nucleus, 2011)
Concentrations of eight metals (Fe, Mn, Cr, Mo, Ni , Pb , Sr and Zn ) in surface sediments of Karachi Coast- Pakistan were determined to evaluate their distribution and pollution assessment. Measured metals in the sediments were found to be in the range of: Fe: 0.84 – 6.96 %, Mn: 300- 1300 µg/g, Cr: 12.0 – 319 µg/g, Mo: 0.49-2.03 µg/g, Ni: 1.53-58.9 µg/g, Pb: 9.0-49.5 µg/g, Sr:192-1185 µg/g, Zn: 15.6-666 µg/g. There is no significant correlations among most of these metals, indicating different anthropogenic and natural sources. To assess ecotoxic potential of marine sediments, Numerical Sediment Quality Guidelines (SQGs) were also applied. The concentrations of Pb in all the sediments were lower than the threshold effect concentration (TECs) showing that there is no harmful effect to marine life from Pb. On the other hand, the concentrations of Cr, Ni and Zn exceeded TEC in three station, indicating their potential risk. The degree of pollution in sediments for metals was assessed by calculating enrichment factor (EF) and pollution load index (PLI). The results indicated that sediments of Layari River Mouth Area, Fish Harbour and KPT Boat Building Area are highly enriched with Cr and Zn (EF > 5). Sediments of Layari River Outfall Zone were moderately enriched with Ni and Pb (EF > 2). The pollution load index was found in the range of 0.98 to 1.34. Lower values of PLI (≤ 1) at most of sampling locations imply no appreciable input from anthropogenic sources. However, relatively higher PLI values (>1) at Layari River Mouth Area, Fish Harbour and KPT Boat Building Area is attributed to increased human activity in the area.